The Impact of Lifestyle, Price and Brand Image on Purchasing Decisions of iPhone Consumers In Semarang City - Septiana, Katherine Grasia; Amron; Cahya, Handy Nur; Zakaria, Fakhmi (Indonesia Banking School, 2025)
The current rapid development of smartphone technology, with innovations increasingly enriching the user experience. iPhones are in high demand due to several key factors that make them different and more attractive to consumers compared to other smartphones. The purpose of this study is to determine how lifestyle, price, and brand image influence iPhone purchasing decisions in Semarang City. The population is people living in Semarang City. This research method is purposive sampling. Data were collected through Google Form and obtained 100 respondents. Using SPSS 24, the research findings show that consumer lifestyle in Semarang City does not significantly influence iPhone purchasing decisions. In Semarang City, iPhone purchasing decisions are influenced by price and brand image. Conclusion: Price and brand image influence purchasing decisions, these variables can increase purchasing decisions, while lifestyle does not influence purchasing decisions. Price and brand image can influence purchasing decisions simultaneously, so companies need to consider these two factors in their iPhone product marketing strategies.